Inetta Nowosad, Klaudia Pietrań, Mirosław J. Szymański (red.), Szkoła. Konflikt Podmiotów? Wydawnictwo Adam Marszałek, Toruń 2016, ss. 266. - Duda, Anna K. (Studia Edukacyjne, 2020)
Recenzja książki Inetta Nowosad, Klaudia Pietrań, Mirosław J. Szymański (red.), Szkoła. Konflikt Podmiotów? Wydawnictwo Adam Marszałek, Toruń 2016, ss. 266.